Some OFF bipolar cell types make contact with both rods and cones in macaque and mouse retinas - Tsukamoto, Yoshihiko; Omi, Naoko (Frontiers in Neuroanatomy, 2014)
This study compared the types of OFF bipolar cells found in the macaque retina with those found in the mouse retina and determined whether these OFF bipolar cells make direct contacts with both rods and cones by serial section transmission electron microscopy. We performed scatter plots and cluster analysis of the morphological variables of their axon terminals such as the stratification level, the arbor thickness, the arbor area, and the number of ribbons. Five OFF bipolar cell types, including the recently discovered DB3b type, were identified in the macaque retina. The macaque OFF bipolar cell types FMB, DB1, DB2, DB3a, and DB3b corresponded to the mouse OFF bipolar cell types 2, 1, 4, 3a, and 3b, respectively. In addition to contacting rod bipolar cells, approximately 7% of rods in the macaque retina made basal contacts exclusively with one cell type, DB3b, whereas 18% of rods in the mouse retina made basal contacts with one or two of types, 3a, 3b, and 4. Approximately 3% of mouse rods were divergently connected to two OFF bipolar cells of different types, but macaque rods were solely connected to one OFF bipolar cell. Rod-rod gap junctions were localized at rod cell bodies and axons in the outer nuclear layer in both macaque and mouse retinas. The direct rod-OFF bipolar connection system is slightly more developed in the mouse retina than in the macaque retina, possibly as a fine-tuned adaptation to nocturnal conditions. This one-step direct synaptic pathway from rods to OFF bipolar cells may enhance the response speed to OFF light stimuli compared with more indirect pathways via rod-cone gap junctions (a two-step pathway) and via rod bipolar and AII amacrine cells (a three-step pathway).